2016
DOI: 10.4322/rca.2560
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência da fertirrigação nitrogenada e potássica do pimentão cultivado em ambiente protegido

Abstract: PALAVRAS-CHAVE Capsicum annuum L. Eficiência nutricional Nutrição mineral KEYWORDS Capsicum annuum L. Nutritional efficiency Mineral nutrition RESUMO:Objetivou-se avaliar a eficiência do uso de nitrogênio (N) e potássio (K) em pimentão cultivado em ambiente protegido, em função de diferentes manejos de fertirrigação. Utilizou-se o delineamento em blocos casualizados, em esquema fatorial 3 × 6, com quatro repetições. Os tratamentos consistiam na combinação de três manejos de fertirrigação (M 1 -fertirrigação a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…As shown in Figure 7, the highest AEK (99.5 kg fruit per kg N) was obtained with 54 kg ha -1 of K in the level N3 (134 kg ha -1 ). Oliveira et al (2016) fertigated sweet pepper and obtained the maximum AEK value (135 kg kg -1 ) when the lowest dose was applied. Those authors concluded that nutritional efficiency was reduced when high doses of K and N were applied.…”
Section: Revmentioning
confidence: 97%
“…As shown in Figure 7, the highest AEK (99.5 kg fruit per kg N) was obtained with 54 kg ha -1 of K in the level N3 (134 kg ha -1 ). Oliveira et al (2016) fertigated sweet pepper and obtained the maximum AEK value (135 kg kg -1 ) when the lowest dose was applied. Those authors concluded that nutritional efficiency was reduced when high doses of K and N were applied.…”
Section: Revmentioning
confidence: 97%
“…Em estudo realizado por Marcussi (2005), Abrahão (2015) e Oliveira et al (2016), dentre outros, é notório que o potássio é o nutriente mais requisitado pela cultura do pimentão. No solo, o potássio movimenta-se por fluxo de massa e difusão e é absorvido pelas raízes na forma iônica.…”
Section: Introductionunclassified
“…Based on this emergency situation, studies on the physiological behaviour of plants under low water availability are required, particularly in melon, in view of its adaptation to edaphoclimatic conditions and its socioeconomic importance. According to studies evaluating melon irrigation (Sensoy, Ertek, Gedik, & Kucukyumuk, 2007;Oliveira, Medeiros, Lima, Dutra, & Oliveira, 2008;Souza, Bezerra, Sousa, & Santos, 2010), some melon types are susceptible to water stress.…”
Section: Introductionmentioning
confidence: 99%